Exploratory Data Analysis on Mathematics Learning Difficulties for Junior High School Students/MTs on Solving Story Problems in Terms of Gender - Yusnita, Irra; Sumarmo, Utari; Fitriani, Nelly (IKIP Siliwangi, 2025)
Mathematics subjects at various levels of education are still considered difficult. One of the mathematical skills that students still lack mastery of is mathematical communication. Otherwise in mathematics learning, as explained in NCTM,